Does Acculturation happen in EFL Context? - Yari, Fariba; Hashemi, Akram (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
In order to understand the second language culture, understanding the nature of acculturation is necessary. Teaching culture should be integrated into the foreign language textbooks and classroom practices. It is necessary for language teachers to integrate cultural materials and values into their teaching and to make them familiar with the culture of the language they are teaching.The aim of this investigation is to magnify the evidence of English Acculturation in Foreign Language Learning Settings (EAFLLS).And to emphasize the significant role of English text books do and have to play in English as a Foreign Language situations.